EFEKTIVITAS HYPERMEDIA KONKRET INTERAKTIF UNTUK MENINGKATKAN KOMPETENSI SISWA SD PADA KELAS TINGGI DAN RENDAH - Yulinda Putri, Gracelia; Nurin Amalina, Farah; Dwijayanti, Ida; Nailul Farichah, Rima (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Elementary school learning requires active, interactive, and student-centered strategies that align with students’ learning characteristics. This study aims to analyze the implementation of inclusive learning assisted by interactive concrete hypermedia and its effectiveness in improving elementary students’ competence. The study employed a quantitative approach using a pre-experimental method with a one group pretest-posttest design. The research subjects consisted of 28 third-grade students and 23 fifth-grade students at SD Supriyadi Semarang. The learning implementation integrated concrete media, interactive visual media, educational games, collaborative activities, differentiated worksheets, learning videos, and smart TV. Data were collected through observation, documentation, reflective journals, and pretest-posttest assessments. Data analysis used the Shapiro-Wilk test and Wilcoxon Signed Rank Test. The findings showed an improvement in students’ learning outcomes and engagement with significance values below 0.05. Therefore, interactive concrete hypermedia is effective in creating more active and student-centered learning.